Inequality of Social Problems Related to the Management and Utilization of Household Waste: Seen from the Perspective of Family Education - Nurul Hayat; Rahmawati Rahmawati; Ibnu Razak; Mokete Nyaphisi Bendly (Universitas Sultan Ageng Tirtayasa, 2023)
Household waste management is an important aspect of sustainable living, which has an impact on environmental welfare and public health. However, the extent to which different socio-economic groups engage in responsible waste management practices varies widely, thereby contributing to broader issues of social inequality. This study investigates how family education, as a key determinant of individual behavior and decision making, influences inequality in waste management practices among various socio-economic groups. Through a comprehensive analysis of existing literature, case studies and empirical data, the author highlights various aspects of social problems related to household waste. From the research results, it was found that 74.4% said that managing waste was easy, 98.5% said they knew how to choose organic and inorganic waste, 82.7% said they knew how to manage and utilize RT waste. However, 61.7% do not carry out real practice of sorting organic and inorganic waste at home independently. It was proven that 51.1% subscribed to rubbish officers in their area and 30.8% disposed of rubbish independently at rubbish dumps. This could be due to a lack of learning in the form of direct practice based on habituation education from home. Supporting this, 78.9% have never taken courses or training regarding the management and use of household waste. And 89.5% of people from the basic family level expressed the need for knowledge, skills and management in the community. These findings highlight the potential of family education programs to bridge the gap in waste management behavior among various socioeconomic strata. Such interventions can empower individuals and families with the knowledge and skills necessary to implement sustainable waste management practices, thereby contributing to a more equitable and environmentally conscious society.